(untitled) (Revista Médica de Trujillo, 2022)
Objetive: Evaluate the quality of doctoral theses at the Faculty of Medicine of the Universidad Nacional Mayor de San Marcos. Methods: Descriptive study, which consisted of the review of 114 theses on health topics in all four doctoral programs - Medicine, Nursing, Health Sciences and Neurosciences - from the creation of the first doctoral program in 1999, until 2020. Four quality indicators were used: scientific problem, sample, analysis (comparability) and conclusions, as well as other complementary indicators to evaluate the writing of the thesis and its social relevance, categorizing them into excellent, acceptable and not acceptable. Results: With the quality indicators there were 32 excellent theses (28.1%), 34 (29.8%) acceptable, and 48 (42.1%) not acceptable. On the other hand, 63 theses (55.2%) had good syntax (acceptable) and in 5 (3.4%) did not make good use of scientific terminology (not acceptable). 17.0% of the theses had both indicators - methodological and writing - of good quality. Conclusion: The doctoral theses evaluated were methodologically acceptable for the most part, with the health sciences theses achieving the best results with the methodological indicators. From the point of view of social impact, most of the theses had social relevance.